Growing up Biden [compact disc, unabridged] - Biden Owens, Valerie, 1945- (Macmillan Audio, 2022)
"A memoir from Valerie Biden Owens, Joe Biden's younger sister, trusted confidante and lifelong campaign manager. Valerie, one of the first female campaign managers in United States history, writes of the role of family, faith, and fate in shaping her life, and the power of empathy and kindness in the face of turmoil and division. Growing Up Biden details Valerie's decades-long professional career in politics, and the central role she played in her brother's life as an insightful adviser, an ever-loyal advocate and best friend. This memoir, full of candor and warmth, brings readers into the Biden home and shares stories from growing up in Delaware as the only daughter of the close-knit Irish Catholic family. Valerie writes in a compelling, relatable way about the challenges she faced breaking through gender barriers, the elusive nature of confidence, and navigating professional responsibilities while raising children" --